Principle of compatibility applied to determination of reaction forces of kinematics pairs - Sanh, Do (Vietnam Journal of Mechanics, 1996)
The aim of investigation is to present the principle of compatibility and to apply it for determining the reaction forces of kinematics pairs in mechanism. For this purpose the system is released from the given constrains. This resulted to increase the number of coordinates of the system. In order that the freed system realizes the motion of the given system, the coordinates of the freed system must satisfy some relations called the constraint equations. The reaction forces of the formed constraints are just the reaction forces, which are of interest to us.